Integration of System Level CFD Simulations into the Development Process of Wind Turbine Prototypes. Issue 5 (September 2020) - Arnold, Matthias; Wenz, Florian; Kühn, Timo; Lutz, Thorsten; Altmikus, Andree
Abstract: During the development process of wind turbines, there is a rising demand for detailed flow and multi-physics analyses. Especially the system level computational fluid dynamics (CFD), focusing not on a single component or aspect, but on the turbine as a system of geometric and dynamic properties can be used to improve the turbine quality and time to market. In this paper the integration of the system level CFD into the development process of Enercon wind turbines is introduced. Further two example applications are detailed presenting the benefits of CFD based nacelle anemometer calibration and a risk assessment study based on aero-servo-elastic CFD simulations.